THE QUALITY OF LIBRARY SERVICES AT STATE JUNIOR HIGH SCHOOL 1 BANUA LAWAS, TABALONG REGENCY. - Djayeng Turano Gunade; Lily Misliani; Siti Naimah (PPPM STIA Amuntai, 2025)
Although many junior high school libraries face challenges in providing adequate services, they possess significant untapped potential. This research identifed several prblematic phonomena, including limeted collention and learning resources, librarian absenteeism, and inadequate infrastructure. The objektive of this study was to determine the quality of library services at SMPN 1 Banua Lawas and the factors influencing it. The results indicate that the quality of library services at SMPN 1 Banua Lawas, Tabalong regency, is fairly good. Indicators showing good service include speed of service, responsiviness, and decisieness. Indicators showing fairly good service include eading room facilities, information provided, timeliness, adherence to standard operating procedures, and attentiveness. Indicator showing poor service include the completeness. Supporting factors include the mobile library program and adherence to SOPs. Inhibiting factors include librarian absenteeism and insufficient budget. To improve service quality, it is recomended that:the principal develop a library funding plan for the upcoming fiscal year; the librarian improve timeliness and on-site presence during working hours; and teachers integrate the library into the teaching and learning process.